The Basic Law of the Hong Kong Special Administrative Region: Economics and Norms of Credibility - Chang, Denis (Columbia Journal of Asian Law, 1988)
Central to the achievement of the Sino-British Joint Declaration on the Question of Hong Kong (Joint Declaration)I was the economic rationale of maintaining the “prosperity and stability” (fanrong anding) of the territory. This declared common objective, while not exclusively confined to the economic sphere, reinforced earlier assur- ances that investors could set their hearts at ease;3 it also proved to be the primary catalyst in the successful completion of the Sino-British accord.4 Not only does the term “prosperity and stability” appear in the Joint Declaration,5 but the Basic Law Drafting Committee (Draft- ing Committee) for the Hong Kong Special Administrative Region (Hong Kong SAR) has since dignified the phrase by enshrining it in the Preamble of the Collection of Draft Provisions of the Basic Law (Collection) and placing it alongside the statement of the national goal of reunification.